Effect of the displacement rate and inclination angle in steel fiber pullout tests - Tarifa, Manuel (2020)
This paper summarizes the results obtained in an experimental campaign on the effect of the displacement pullout rate and the inclination angle of the steel fiber pullout tests. For that purpose, specimens were obtained from a self-compacting concrete with a compressive strength of 86 MPa. In the experimental program, hooked-end steel fibers of 0.75 mm diameter and 60 mm length were used. Tests were executed with both hooked-end fibers, and smooth fibers obtained from the former by cutting the hooked end. For both type of fibers, their embedment length into concrete was 20 mm, and the influence of fiber inclination angle toward the load direction was investigated by adopting values of 0∘, 30∘ and 60∘. The tests were performed at displacement rates of 0.01, 0.1 and 1 mm/s. The results have shown that the peak pullout load increased with the inclination angle, in particular for the smooth series. Furthermore, higher displacement rates led to a higher energy absorption capacity for the pullout of the smooth fibers, while the energy absorption remained almost stable for hooked-end fibers.